The Immediate Effect of Protective Knee Brace application on the Ground Reaction Forces of People with Genu Valgum During Landing - M Barghamadi; K Shahbazioghli; E Piri; Kh Alapour; A Nosratihashi; H Allahverdidost (Journal of Paramedical Science and Rehabilitation)
Purpose:Genu valgum is one of the most important lower limb abnormalities that puts athletes at risk of injury due to weight imbalance in the inner and outer parts of the knee. The aim of the present study was to evaluate the immediate effect of protective knee braces on the ground reaction forces of people with genu valgum during landing.Methods:The present study was a semi-experimental laboratory study. In this study, 10 boys with genu valgum (with an average age (years): 21.71 ± 2.28, height (m): 1.89 ± 0.07, weight (kg): 74.69 ± 10.56, and body mass index (kg/m2): 23.64 ± 0.85) in the experimental group and 10 healthy (with average age (years): 23.14 ± 2.96, height (m): 1.82 ± 0.06, weight (kg): 75.14 ± 9.89 and body mass index (kg/m2): 24.77 ± 1.98) boys who did not have any lower limb disorders were selected as the control group. A three-axis force plate device Bertec (Corporation, Columbus, OH) was used to record ground reaction force information. For statistical analysis, SPSS V21 software and analysis of variance with repeated measures were used at a significant level of 0.05.Results:Between group results showed that the peak of the vertical component (p=0.002) and the time to reach the peak of the vertical component (p=0.004) of the ground reaction force had a significant difference in the control and genu valgum groups. The inter-group results showed that the peak of the vertical component (p<0.001) and the time to reach the peak of the vertical component (p<0.001) of the ground reaction force in the genu valgum group in the post-test compared to the pre-test had a significant decrease of 44.3 and 34.9%, respectively.Conclusion:According to the research results, it can be concluded that the use of knee brace in these people has been able to increase the protective efficiency in the knee joint and cause force absorption during landing. Therefore, perhaps the long-term application of this type of protective brace can improve other components of the ground reaction force.